Respuesta :

Answer:2nd option

Hope this helps you...

Step-by-step explanation:

Ver imagen bridebenson007

Answer:

Choice B is correct answer.

Step-by-step explanation:

We have given a quadratic equation.

7x²-x =  7

7x²-x-7 =  0

ax²+bx+c = 0 is general quadratic equation.

x =(-b±√b²-4ac) / 2a is quadratic formula to solve equation.

comparing general equation with given equation, we have

a = 7 , b= -1 and c = -7

Putting above values in quadratic formula , we have

x = (-(-1)±√(-1)²-4(7)(-7) ) / 2(7)

x = (1 ±√1+196) / 14

x = (1±√197) / 14 which is the answer.

ACCESS MORE